Degradation of hydrocarbon components contaminated in oily waste-water collected in Doxa petroleum storage, Hanoi by microbial biofilm attached on coconut fiber - Do, Tuan Van; Le, Cong Thi Nhi; Do, Lien Thi; Dong, Quyen Van (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Oily waste-water is generated in many industrial processes, such as oil refining, oil storage, exploration, transportation, washing ... Oily waste water poses a great problem with water environment, ecosystem and human health. Nowadays, application of microbial biofilm for the removal of oil and derivatives from contaminated environments has received much attention. Microbial biofilms are defined as complex coherent structure of cells and cellular products, which are attached on solid surface. In biofilm structure, microorganisms increase their ability to grow and survive in changing environmental conditions and increase their access to absorb substrates or nutrients. This study focused on the degradation of hydrocarbon components contaminated in oil polluted waste water by biofilm formed by a mixture of bacterial and yeast strains isolated from oil contaminated water in Viet Nam attached on coconut fiber carriers in 2000 liter system. As the results, biofilm attached on coir carrier could degrade 62% after 5 days and 99,9% after 7 days of the total amount of oil with the initial concentration of 31.950 mg/l. Phenol and polycyclic aromatic hydrocarbons (PAHs) also were degraded up to 99.9% phenol and more than 94,8%PAHs in oily wastewater. This result gave hint to develop new method to treat petroleum oil contaminated water in Vietnam.